Penguatan Kerangka Regulasi untuk Mendukung Inovasi dan Kewirausahaan di Era Ekonomi Digital - Anugrah, Bintang Dewa; Efendy, Efendy; Irlan, Irlan; Susilo, Susilo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The role of law in promoting innovation and entrepreneurship in the digital era is crucial in creating a sustainable and conducive economic ecosystem. Law functions to provide legal certainty and protection for business actors, particularly through regulations concerning intellectual property rights, personal data protection, and consumer protection within digital economic activities. Adaptive regulations not only safeguard innovators from potential violations of their rights but also ensure fair and ethical business competition. In Indonesia, digitalization has significantly transformed business processes and licensing systems, thereby improving the ease of doing business and supporting economic growth. Therefore, the harmonization of business law with technological developments is essential to maintain a balance between innovation, security, and legal certainty, ultimately strengthening national competitiveness in the global market.